DNA metabarcoding of fungal diversity in air and snow of Livingston Island, South Shetland Islands, Antarctica - Rosa, Luiz Henrique (Sci Rep, 2020)
We assessed fungal diversity present in air and freshly deposited snow samples obtained from Livingston Island, Antarctica, using DNA metabarcoding through high throughput sequencing (HTS). A total of 740 m(3) of air were pumped through a 0.22 µm membrane. Snow obtained shortly after deposition was kept at room temperature and yielded 3.760 L of water, which was filtered using Sterivex membranes of 0.22 µm mesh size. The total DNA present was extracted and sequenced. We detected 171 fungal amplicon sequence variants (ASVs), 70 from the air and 142 from the snow. They were dominated by the phyla Ascomycota, Basidiomycota, Mortierellomycota and Mucoromycota. Pseudogymnoascus, Cladosporium, Mortierella and Penicillium sp. were the most dominant ASVs detected in the air in rank order. In snow, Cladosporium, Pseudogymnoascus, Penicillium, Meyerozyma, Lecidea, Malassezia, Hanseniaspora, Austroplaca, Mortierella, Rhodotorula, Penicillium, Thelebolus, Aspergillus, Poaceicola, Glarea and Lecanora were the dominant ASVs present. In general, the two fungal assemblages displayed high diversity, richness, and dominance indices, with the assemblage found in snow having the highest diversity indices. Of the total fungal ASVs detected, 29 were only present in the air sample and 101 in the snow sample, with only 41 present in both samples; however, when only the dominant taxa from both samples were compared none occurred only in the air and, among the rare portion, 26 taxa occurred in both air and snow. Application of HTS revealed the presence of a more diverse fungal community in the air and snow of Livingston Island in comparison with studies using traditional isolation methods. The assemblages were dominated by cold-adapted and cosmopolitan fungal taxa, including members of the genera Pseudogymnoascus, Malassezia and Rhodotorula, which include some taxa reported as opportunistic. Our results support the hypothesis that the presence of microbiota in the airspora indicates the possibility of dispersal around Antarctica in the air column. However, further aeromycology studies are required to understand the dynamics of fungal dispersal within and beyond Antarctica.